Strategic thinking: construction and validation of an instrument - Rodrigues, R.; Ferreira, A.I.; Neves, J. (14th ECPA 2017, 2017)
The present research aims to present the development of a Strategic Thinking Questionnaire (QPE). In the first study, an exploratory factorial analysis was carried out, from which three dimensions were extracted: strategic thinking, future vision and identification of new opportunities which from the psychometric point of view have shown to be adequate. The sample is consisted of 272 subjects aged 25-59 years (M = 41.14; SD = 9.14). A second study with a confirmatory factorial analysis, in which 352 human resources professionals, ranging in age from 26 to 56 years old (M = 38.74; SD = 9.51) participated, replicated the same three factors and showed a good adjustment of the fashion model. The results obtained allow likewise gathering consistent evidence about the convergent validity. The pertinence of the study is associated with the lack of an instrument that evaluates uniquely the strategic thinking and by fact that itself is positively related to high levels of professional performance.